"As rare as a panda": How facial attractiveness, gender, and occupation affect interview callbacks at Chinese firms. Issue 1 (7th April 2015) - Maurer-Fazio, Margaret; Lei, Lei
Abstract : Purpose: – The purpose of this paper is to explore how both gender and facial attractiveness affect job candidates' chances of obtaining interviews in China's dynamic internet job board labor market. It examines how discrimination based on these attributes varies over occupation, location, and firms' ownership type and size. Design/methodology/approach: – The authors carry out a resume audit (correspondence) study. Resumes of fictitious applicants are first carefully crafted to make candidates appear equally productive in terms of their work histories and educational backgrounds. The authors control gender and facial attractiveness. The authors establish the facial attractiveness of candidate photos via an online survey. In total, 24, 192 applications are submitted to 12, 096 job postings across four occupations in six Chinese cities. Callbacks are carefully tracked and recorded. Discrimination is estimated by calculating the differences in the rates of callbacks for interviews received by individuals whose applications vary only in terms of facial attractiveness and gender. The authors reuse the same resumes repeatedly through this project such that names and photos of each of the candidates: attractive man, attractive woman, unattractive man, and unattractive woman is attached to each resume hundreds of times for each occupation in each city. Findings: – The authors find sizable differences in the interview callback rates of attractive and unattractive job candidates. Job candidates with unattractive faces need to put in 33 percent more applications than their attractive counterparts to obtain the same number of interview callbacks. Women are preferred to men in three of the four occupations. Women, on average need put in only 91 percent as many applications as men to obtain the same number of interview callbacks. Research limitations/implications: – The analysis of this paper focusses on only four different occupations. Its scope is also limited to exploring only the first part of the hiring process – obtaining a job interview. Furthermore, its fictitious applicants are all young people, approximately 25 years old. It would be useful to explore how gender and facial attractiveness affect candidates' chances of landing a job after getting an interview. Originality/value: – This paper contributes to and expands the literature on hiring through China's internet job boards. It also contributes to the literature on the role of facial attractiveness in hiring.